Length-Weight Relationship, Fultonâ€™s Condition Factor and Sex Ratio of Nile Perch (Lates niloticus, Linnaeus- 1762) in Lake Abaya, Ethiopia - Shizha, Shishitu Buchale (Journal of Agriculture and Environmental Sciences, 2022)
The length-weight relationship of fish is an important fishery management tool. The objectives of the study were to determine the length-weight relationship, Fultonâ€™s condition factor and the sex ratio of Lates niloticus in Lake Abaya. Total length (TL), total weight (TW), and sex data were collected from 755 fish samples (377 females and 378 males) for one year (January to December 2021) from the commercial fishery of Lake Abaya. The collected data were summarized by using descriptive statistics and analyzed with the application of Microsoft Excel 2010 and SPSS software. There was no significant deviation in sex ratio (M: F) from hypothetical 1:1 ratio (Ï‡2 = 0.00; P > 0.05). The length-weight relationship was calculated using power function and obtained as TW = 0.0077*TL3.1176, (R2 = 0.8834), TW = 0.0078*TL3.1372, (R2 = 0.8548) and TW = 0.0098*TL3.0723, (R2 = 0.8713) for females, males and combined sexes, respectively. The regression coefficient â€œbâ€ was significantly different from the cubic value â€œ3â€ (P<0.05) and implied that L. niloticus of Lake Abaya follows a positive allometric growth pattern. The one-way ANOVA (P > 0.05) revealed that Fultonâ€™s condition factor between sexes was insignificant but highly significant by monthâ€™s interaction (ANOVA, P < 0.05). The t-test also revealed a highly significant difference in a monthâ€™s interaction (t-test, P = 0.000) indicating the seasonal variation in the mean monthly condition factor. The average value of Fultonâ€™s condition factor was higher than one and indicates that L. niloticus in Lake Abaya was in good health condition. The present study was focused only on L. niloticus and recommends that similar studies including feeding and reproductive biology should be conducted to determine the status of other fish species in Lake Abaya. Keywords: Allometric growth pattern, Commercial fishery, Fishery management, freshwater fish, Lake Fishery